Opium abuse and stroke in Iran: A systematic review and meta-analysis - Mardi, Parham (Frontiers in Neurology, 2022)
Introduction: Opium dependence is a significant health concern in low and middle-income countries, leading to a considerable number of deaths annually. Opium has several detrimental effects on its consumers. Data regarding the impact of opium on stroke is controversial. The objective of this study is to evaluate the association between opium dependence and stroke. Methods: I conducted a systematic search based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to evaluate the association between opium dependence and stroke. Following the extraction of qualitative findings of included studies, a meta-analysis was performed to assess the pooled estimate of odds ratios (ORs). Results: Eight and four studies were included in qualitative and quantitative synthesis, respectively. Opium dependence increases the hazard of stroke mortality. Also, opium increases the odds of ischemic stroke by 127 percent (pooled OR= 2.27, 95%CI: 1.47-3.07). Conclusion: Opium does not merely increase the odds of being diagnosed with ischemic stroke but also leads to a notable increase in mortality rate following stroke.